Genome Sequencing and Analysis of the Peanut B-Genome Progenitor (Arachis ipaensis) - Lu, Qing; Li, Haifen; Hong, Yanbin; Zhang, Guoqiang; Wen, Shijie; Li, Xingyu; Zhou, Guiyuan; Li, Shaoxiong; Liu, Hao; Liu, Haiyan; Liu, Zhongjian; Varshney, Rajeev K.; et al. (Frontiers in Plant Science, 2018)
Peanut (Arachis hypogaea L.), an important leguminous crop, is widely cultivated in tropical and subtropical regions. Peanut is an allotetraploid, havingA and B subgenomes that maybe have originated in its diploid progenitors Arachis duranensis (A-genome) and Arachis ipaensis (B-genome), respectively. We previously sequenced the former and here present the draft genome of the latter, expanding our knowledge of the unique biology of Arachis. The assembled genome of A. ipaensis is ~1.39 Gb with 39,704 predicted protein-encoding genes. A gene family analysis revealed that the FAR1 family may be involved in regulating peanut special fruit development. Genomic evolutionary analyses estimated that the two progenitors diverged ~3.3 million years ago and suggested that A. ipaensis experienced a whole-genome duplication event after the divergence of Glycine max. We identified a set of disease resistance-related genes and candidate genes for biological nitrogen fixation. In particular, two and four homologous genes that may be involved in the regulation of nodule development were obtained from A.ipaensis and A.duranensis, respectively. We outline a comprehensive network involved in drought adaptation. Additionally, we analyzed the metabolic pathways involved in oil biosynthesis and found genes related to fatty acid and triacylglycerol synthesis. Importantly, three new FAD2 homologous genes were identified from A. ipaensis and one was completely homologous at the amino acid level with FAD2 from A.hypogaea. The availability of the A. ipaensis and A. duranensis genomic assemblies will advance our knowledge of the peanut genome.